Awakening and Wandering of Modern Consciousness During the May Fourth Period: A Case Study of Ding Ling’s Miss Sofia’s Diary and Meng Ke - Li, Yanyan (Transactions on Social Science, Education and Humanities Research, 2024)
Miss Sofia’s Diary and Meng Ke are both novels by Ding Ling in the late 1920s. The publication of Miss Sofia’s Diary caused a great sensation in the literary world at that time, which has been praised by some commentators as "a bomb dropped in this dead literature". The heroine Sofia is the representative of ideological emancipation during the May Fourth Period. Meanwhile, Meng Ke, Ding Ling's first short story, also reflects the awakening of women's modern consciousness in the times and gradually grasps the "self" discourse. This paper analyzes Ding Ling's modern consciousness and the reasons for women's awakening and wandering during the May Fourth Period, so as to explore the significance of Miss Sofia’s Diary and Meng Ke to the literature of the same period and modern women.